PERAN TATA KELOLA PERUSAHAAN SEBAGAI PEMODERASI GREEN ACCOUNTING, KINERJA LINGKUNGAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Kurniati, Septia; Minar Savitri, Dhian Andanarini (Universitas Sarjanawiyata Tamansiswa, 2025)
Environmental damage is often caused by nature, besides it can also be due to human intervention such as industrial activities that often neglect the impact on the surrounding environment. The aim of this research is to identify and analyse how corporate governance affects corporate performance, environmental performance, and size of the company. Thro 2019-2022, there were 143 samples of companies in the sub-sector of food and food materials sales, baverage, and process food. In this study, the double linear regression analysis was performed using the SPSS program version 25. There were 39 companies that met the criteria for the research, so sampling was selected purposively. Analysis results show that green accounting does not have a significant impact on corporate performance; however, corporate size and environmental performance have a positive and significant effect on financial performance; and corporate governance has the capacity to improve environmental accounting, and the size of an enterprise on its performance.